Adverse Health Effects of Betel Quid and the Risk of Oral and Pharyngeal Cancers. (11th December 2017) - Chen, Ping-Ho; Mahmood, Qaisar; Mariottini, Gian Luigi; Chiang, Tai-An; Lee, Ka-Wo
Abstract : Global reports estimate 600 million betel quid (BQ) chewers. BQ chewing has been demonstrated not only to be a risk factor for cancers of the oral cavity and pharynx and oral potentially malignant disorders (OPMD) but also to cause other cancers and adverse health effects. Herein, we summarized the international comparison data to aid in the understanding of the close relationship between the prevalence of BQ chewing, the occurrence of oral and pharyngeal cancers, and adverse health effects. Potential biomarkers of BQ carcinogens, such as areca nut, alkaloids, and 3-methylnitrosaminopropionitrile (MNPN), are closely associated with human health toxicology. Molecular mechanisms or pathways involving autophagy, hypoxia, COX-2, NF- κ B activity, and stemness are known to be induced by BQ ingredients and are very closely related to the carcinogenesis of cancers of oral and pharynx. BQ abuse-related monoamine oxidase (MAO) gene was associated with the occurrence and progress of oral and pharyngeal cancers. In summary, our review article provides important insights into the potential roles of environmental BQ (specific alkaloid biomarkers and nitrosamine products MNPN) and genetic factors (MAO) and offers a basis for studies aiming to reduce or eliminate BQ-related OPMD and oral/pharyngeal cancer incidences in the future.